2019
DOI: 10.1016/j.psyneuen.2019.104409
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent associations between maternal prenatal cortisol and child callous-unemotional traits: Findings from the Wirral Child Health and Development Study

Abstract: HighlightsPrenatal maternal cortisol predicts child behaviours up to age 5 years.The association shows marked sex differences.Higher cortisol is associated with lower callous-unemotional traits only in girls.Higher cortisol is not associated with child anxious-depressed symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Mothers unable to understand the German language, in advanced pregnancy (> 19 weeks) or not able to participate in laboratory assessments five months after childbirth were not included into the study. One-hundred and eight mothers took part in the initial assessments during pregnancy (see [ 43 , 44 ] for the course and interrelations of prenatal stress measures and infant development). Assessments took place during the first trimester (t1), second trimester (t2) and third trimester (t3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers unable to understand the German language, in advanced pregnancy (> 19 weeks) or not able to participate in laboratory assessments five months after childbirth were not included into the study. One-hundred and eight mothers took part in the initial assessments during pregnancy (see [ 43 , 44 ] for the course and interrelations of prenatal stress measures and infant development). Assessments took place during the first trimester (t1), second trimester (t2) and third trimester (t3).…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies investigating sex interaction effects reported opposite effects depending on sex: Whereas higher cortisol predicted more emotional reactivity in girls, it predicted less emotional negativity [ 42 ] and less emotional reactivity [ 43 ] in boys. Another study found lower callous-emotional traits in girls exposed to higher prenatal cortisol, but no effect for boys [ 44 ]. Overall, while studies investigating sex-dependent effects of prenatal maternal cortisol are still too sparse to identify a comprehensive pattern, the ones that exist relatively consistently report sex differences in response to prenatal stress.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Elevated maternal prenatal cortisol was also associated with lower child callousunemotional traits in female offspring, but not in male offspring at 2.5-5.0 years of age. 39 Wei et al reported that higher maternal prenatal depressive symptoms were associated with greater cortical surface area in male offspring and lower surface area in female offspring at 2 and 6 months of age, specifically in areas of the prefrontal cortex, superior temporal gyrus, and superior parietal lobule. 40 For reference, sex differences have been observed among rodents.…”
Section: Sex Differencesmentioning
confidence: 99%
“…28,29 Wright et al reported that an elevated maternal prenatal cortisol level was associated with lower callous-unemotional traits in girls, but not in boys, at 2.5-5.0 years of age. 30 As this study was based solely on K6 points based on the questionnaire and did not examine cortisol levels, future studies are needed to determine how the effects of K6 trajectories and cortisol levels on children differ by sex.…”
Section: Sex-specific Differencesmentioning
confidence: 99%